Control of sleep-to-wake transitions via fast amino acid and slow neuropeptide transmission - Thiago Mosqueiro; Luis de Lecea; Ramon Huerta (New Journal of Physics, 2014)
The locus coeruleus (LC) modulates cortical, subcortical, cerebellar, brainstem and spinal cord circuits and it expresses receptors for neuromodulators that operate on a time scale of several seconds. Evidence from anatomical, electrophysiological and optogenetic experiments has shown that LC neurons receive input from a group of neurons called hypocretin neurons that release a neuropeptide called hypocretin. It is less well known how these two groups of neurons can be coregulated using GABAergic (GABA standing for gamma aminobutyric acid) neurons. As the time scale for GABA _A inhibition is several orders of magnitude faster than that for the hypocretin neuropeptide effect, we investigate the limits of circuit activity regulation using a realistic model of neurons. Our investigation shows that GABA _A inhibition is insufficient to control the activity levels of the LCs. Although slower forms of GABA _A can in principle work, there is not much plausibility due to the low probability of the presence of slow GABA _A and lack of robust stability at the maximum firing frequencies. The best possible control mechanism predicted by our modeling analysis is the presence of inhibitory neuropeptides, which exert effects on a similar time scale to the hypocretin/orexin. Although the nature of these inhibitory neuropeptides has not been identified yet, it provides the most efficient mechanism in the modeling analysis. Finally, we present a reduced mean-field model that perfectly captures the dynamics and the phenomena generated by this circuit. This investigation shows that brain communication involving multiple time scales can be better controlled by employing orthogonal mechanisms of neural transmission to decrease interference between cognitive processes and hypothalamic functions.